Sastra dan cultural studies : representasi fiksi dan fakta - Ratna, Nyoman Kutha (Yogyakarta : Pustaka Pelajar, 2005)
Role of literature in cultural aspect of Indonesia
Daftar pustaka : p. 581-590
Keywords: Indonesian literature -- Study and teaching; Indonesian literature -- History and criticism; Literature and society